Pemikiran Inklusif M. Quraish Shihab dalam Moderasi Beragama di Indonesia (1983-2025 M) - Rahma Afa Muflikhuna; Rakhela Sayyidatun Najah; Anas Salsabil; Latifatur Rohmah (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Indonesia's religious and cultural diversity necessitates the strengthening of religious moderation capable of maintaining a balance between religious commitment and respect for pluralism. This study aims to analyze the concept, implementation, and relevance of M. Quraish Shihab's inclusive thought in promoting religious moderation in Indonesia during the period of 1983-2025. The research employs a historical method with a qualitative approach through the stages of heuristics, source criticism, interpretation, and historiography, focusing on M. Quraish Shihab's scholarly works and relevant academic literature. The findings reveal that M. Quraish Shihab's inclusive thought has developed consistently through a dialogue between the Qur'an, the tradition of Qur'anic exegesis, and the realities of Indonesia's pluralistic society. The concept of wasathiyyah is understood as a principle of balance grounded in justice, public benefit (maslahah), and respect for human dignity. Its implementation is reflected in Tafsir Al-Misbah and his other scholarly works, which contextualize Qur'anic teachings within the spheres of social life, education, and nation-building. This study concludes that M. Quraish Shihab's inclusive thought constitutes a significant intellectual foundation for strengthening religious moderation in Indonesia. The novelty of this research lies in its historical reconstruction, which comprehensively integrates the evolution of the concept, implementation, and contribution of M. Quraish Shihab's inclusive thought throughout the 1983-2025 period.